Rancang Bangun Prototype Sistem Peringatan Dini Banjir Berbasis Mikrokontroler ESP32 dengan Teknologi Lora dan Platform Thingspeak - Atilah Alfusiah; Almasri Almasri; Titi Sri Wahyuni; Edidas Edidas (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
This study aims to design and develop a flood early warning system prototype based on the ESP32 microcontroller using LoRa communication technology and integration with the ThingSpeak platform as an Internet of Things (IoT) monitoring system. The system was developed to address the limitations of previous flood monitoring systems, which were constrained by limited communication range and the lack of real-time information delivery to the public. The development method used is the Waterfall model, consisting of requirement analysis, system design, implementation, and testing stages. The system consists of a transmitter unit equipped with an ultrasonic sensor, a water level sensor, and a water flow sensor used to detect water height and flow conditions. The sensor data is processed by the ESP32 microcontroller and transmitted via a LoRa module to the receiver unit. On the receiver side, the ESP32 is connected to the internet to send data to the ThingSpeak platform, enabling real-time monitoring in the form of graphs and flood status indicators. The results show that the system is capable of accurately detecting changes in water level and flow while providing a wider communication range compared to previous nRF-based systems. The integration of LoRa offers advantages in power efficiency and transmission distance, while the ESP32 ensures stable IoT connectivity. Therefore, this prototype can serve as an effective, fast, and accessible alternative flood early warning system to support disaster mitigation in flood-prone areas.